FOXR2 stabilizes MYCN protein and identifies non-MYCN-amplified neuroblastoma patients with unfavorable outcome - Schmitt-Hoffner, Felix; van Rijn, Sjoerd; Toprak, Umut; Mauermann, Monika; Rosemann, Felix; Heit-Mondrzyk, Anke Claudia; Hübner, Jens-Martin; Camgöz, Aylin; Stainczyk, Sabine; Pfister, Stefan; Henrich, Kai-Oliver; Westermann, Frank; et al. (Journal of clinical oncology, 2021)
Clinical outcomes of patients with neuroblastoma range from spontaneous tumor regression to fatality. Hence, understanding the mechanisms that cause tumor progression is crucial for the treatment of patients. In this study, we show that FOXR2 activation identifies a subset of neuroblastoma tumors with unfavorable outcome and we investigate the mechanism how FOXR2 relates to poor outcome in patients.